Impact of spirituality at workplace on organizational commitment in private banks of Nagpur, India - S. I. Khan (Путеводитель предпринимателя, 2021)
Scholars report that, researchers and management professionals have steady increased their interest in spiritual issues at work. The concept of spirituality in life workplace has become more and more popular in recent years. This research is carried mainly to understand the relationship between workplace spirituality & organizational commitment. It was also studied the impact of spirituality on the commitment of employees from bank. For this research, four private banks were selected. Total 218 employees were randomly picked for this study. SPSS, version 23 was utilized for evaluating the data. It was found that spirituality strongly influences the organizational commitment, and it directly impacts on it. It was suggested that the management should consider spirituality at workplace seriously in order to enhance the productivity of employees, and they will be more committed towards their work.